1999
DOI: 10.1161/01.cir.99.19.2523
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Antagonists Ameliorate Ischemia-Induced Endothelial Cell Permeability by Inhibiting Protein Kinase C

Abstract: Background-Dihydropyridines block calcium channels; however, they also influence endothelial cells, which do not express calcium channels. We tested the hypothesis that nifedipine can prevent ischemia-induced endothelial permeability increases by inhibiting protein kinase C (PKC) in cultured porcine endothelial cells. Methods and Results-Ischemia was induced by potassium cyanide/deoxyglucose, and permeability was measured by albumin flux. Ion channels were characterized by patch clamp. [Ca 2ϩ ] i was measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 44 publications
1
37
2
Order By: Relevance
“…27 We observed an effect of amlodipine on PKC isoforms ␣ and ␤, but not ␦ or . The importance of PKC-␣ and -␤ during cell adhesion has been previously reported, 27,28 as Sun et al 28 showed that overexpression of PKC-␣ enhanced the motility and adhesion of breast cancer cells and Nonaka et al 29 found that inhibition of PKC-␤ resulted in reduced entrapment of leukocytes in rat diabetic retina models.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…27 We observed an effect of amlodipine on PKC isoforms ␣ and ␤, but not ␦ or . The importance of PKC-␣ and -␤ during cell adhesion has been previously reported, 27,28 as Sun et al 28 showed that overexpression of PKC-␣ enhanced the motility and adhesion of breast cancer cells and Nonaka et al 29 found that inhibition of PKC-␤ resulted in reduced entrapment of leukocytes in rat diabetic retina models.…”
Section: Discussionmentioning
confidence: 63%
“…One possible explanation is that amlodipine interferes with the release of phospholipid components, such as diacylglycerol, from the plasma membrane to activate PKC. 27 As previously reported, disturbance of this phospholipid would dramatically affect PKC signaling. 30 Furthermore, the unique characteristics of amlodipine that cause it to exhibit a strong and sustained affinity to the lipid bilayer might play a role in the amlodipine-dependent reduction of THP-1 cell adhesion.…”
Section: Discussionmentioning
confidence: 69%
“…Consequently myocardial ischaemia was easily induced, and likely to have been repetitive. Circumstances that are known to increase endothelial permeability, 15 possibly explaining the relatively high transfection efficiency. The relevance of the study by Giordano et al 14 to patients with ischaemic heart disease was immediately obvious.…”
Section: Discussionmentioning
confidence: 99%
“…These studies support a prominent role of different PKC isoforms in microvascular leakage associated with different pro-inflammatory mediators. Increased PKC activity has also been associated with various vascular disorders such as atherosclerosis, hypoxia, and ischemia reperfusion (138,174,286,447).…”
Section: Pkcsmentioning
confidence: 99%